2016
DOI: 10.1111/odi.12566
|View full text |Cite
|
Sign up to set email alerts
|

Buccally impacted maxillary canines increase the likelihood of root separation in adjacent first premolars

Abstract: Buccally impacted maxillary canines are associated with an increased prevalence of root separation in the adjacent maxillary first premolars. This is likely because that buccally impacted canines encroach on the space needed for root development of the first premolars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…The configuration of the first premolar showed a high link to canine impaction in the present study; 53% of impaction was associated with a separated root configuration. This is in line with Cao et al [ 30 ], who found that separated roots have a higher incidence of impaction.…”
Section: Discussionsupporting
confidence: 92%
“…The configuration of the first premolar showed a high link to canine impaction in the present study; 53% of impaction was associated with a separated root configuration. This is in line with Cao et al [ 30 ], who found that separated roots have a higher incidence of impaction.…”
Section: Discussionsupporting
confidence: 92%
“…The accuracy of measurement recorded by CT and CBCT machines has been reported on by several authors (Loubele et al, 2008). Although it can be concluded that CBCT systems render anatomical measurements reliably and are an appropriate tool for linear measurements (Patcas et al, 2012), the level of accuracy and inter‐operator error may be affected by visual limitations, or when measuring small cross‐sectional bone dimensions (Cao et al, 2017; Leung et al, 2010; Patcas et al, 2012; Wood et al, 2013). This is particularly important when immature or newly forming bone tissue may have a reduced bone density (Januario et al, 2011; Marmulla et al, 2005).…”
Section: Discussionmentioning
confidence: 99%